PENERAPAN MEDIA LOOSE PART MELALUI RAGAM AKTIVITAS MOTORIK HALUS PADA USIA 4 – 5 TAHUN DI TK ISLAM AD-DAHIRIYYAH JOGLO, JAKARTA BARAT - Delly Yanti Amiyana; Dwi Puji Lestari; Huda S Kamalie (Universitas Darunnajah, 2026)
This research is motivated by the low fine motor skills of children aged 4-5 years which can be seen from the difficulty of children in carrying out activities of picking, attaching, and arranging materials. This study aims to describe a variety of fine motor activities through the use of Loose Part media and analyze its impact on early childhood development. The research used a descriptive qualitative approach which was carried out at Ad-Dahiriyyah Joglo Islamic Kindergarten, West Jakarta. The research subjects were children aged 4-5 years. Data collection techniques are carried out through observation, interviews, and documentation, then analyzed descriptively. The results of the study showed that a variety of fine motor activities through the Loose Part media included pattern drawing, squeezing, pinching, and sticking. These activities are able to stimulate children's fine motor development, such as finger muscle strength, hand-eye coordination, concentration, patience, and neatness. In addition, this activity also has an impact on increasing creativity, confidence, and habituation of Islamic values through learning that begins with prayer and gratitude. It was concluded that the application of Loose Part media through a variety of activities had a positive impact on the fine motor development of children aged 4–5 years.